Iron-silicon composite magnetic powder core and preparation method and application thereof

By compositeing high ferrosilicon silicon magnetic powder and low ferrosilicon silicon magnetic powder and specific processing steps, the problems of low density and high cost of ferrosilicon composite magnetic materials in the prior art are solved, and a composite magnetic powder core with high density, excellent thermal stability and low magnetic loss are prepared.

CN119517600APending Publication Date: 2025-02-25HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411733260.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The ferrosilicon composite magnetic material prepared in the prior art has the defect of low density and high cost, and it is difficult to produce a high density and excellent magnetic performance at low cost.

Method used

By combining high ferrosilicon silicon magnetic powder and low ferrosilicon silicon magnetic powder, the silicon content range of high ferrosilicon silicon magnetic powder is limited, and after mixing, passivation, insulation coating, press molding and annealing treatment are performed, the prepared composite magnetic powder core has high density and excellent thermal stability.

Benefits of technology

The high density, low magnetic loss and excellent thermal stability of the composite magnetic powder core are achieved, while reducing production costs and improving magnetic permeability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of an iron-silicon composite magnetic powder core, which comprises the following steps of: mixing high-silicon iron-silicon magnetic powder and low-silicon iron-silicon magnetic powder to obtain mixed iron-silicon powder, and sequentially performing passivation, insulating coating, compression molding and annealing treatment to obtain the iron-silicon composite magnetic powder core. The composite magnetic powder core is prepared by compounding the high-silicon iron silicon magnetic powder and the low-silicon iron silicon magnetic powder. Wherein the magnetic performance of the high-silicon iron silicon magnetic powder is excellent, the silicon content of the high-silicon iron silicon magnetic powder is limited within a certain range, the magnetic conductivity of the magnetic powder core can be improved, the magnetic loss can be reduced, however, the prepared magnetic powder core is low in density and high in cost, and the thermal stability of the magnetic powder core can be affected; the low-silicon iron silicon magnetic powder is soft in texture, low in cost and easy to form. The prepared composite magnetic powder core is high in density, high in thermal stability, high in magnetic conductivity and low in magnetic loss.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnetic powder cores, in particular to an iron-silicon magnetic powder core and a preparation method and application thereof, and in particular to an iron-silicon composite magnetic powder core and a preparation method and application thereof. Background Art

[0002] With the development of science and technology, various types of soft magnetic powder cores are widely used in new energy, electrical, communication and automotive industries, requiring various types of soft magnetic powder cores to develop in the direction of miniaturization, intelligence, high integration and low loss. At present, there are mainly various types of soft magnetic powder cores on the market, such as iron powder cores and non-ferrous metal magnetic powder cores. Among them, iron powder cores have higher saturation magnetic induction intensity, but lower resistivity. They are usually used in low frequency bands and have large eddy current losses at high frequencies. Although the loss of non-ferrous metal magnetic powder cores is greatly reduced compared to iron powder cores, the DC superposition characteristics and high-frequency losses still limit their large-scale application.

[0003] Among non-ferrous metal magnetic powder cores, iron silicon magnetic powder cores are widely used because of their cost advantages and high DC superposition performance, although they have high losses and serious heat generation. CN111029076A discloses an atomized iron silicon aluminum soft magnetic composite material with low medium frequency loss. The soft magnetic composite material is prepared by using atomized iron silicon aluminum powder with three particle size ranges. The magnetic core loss at 50kHz / 100mT is not higher than 175mW / cm 3 However, the soft magnetic composite material prepared by the invention has low density and high cost, which is not conducive to large-scale industrial production.

[0004] The iron-silicon composite magnetic materials prepared in the prior art have the defects of low density and high cost. Therefore, how to prepare the iron-silicon composite magnetic materials with high density and excellent magnetic properties at low cost has become a problem that needs to be solved urgently. Summary of the invention

[0005] In order to solve the above technical problems, the present invention discloses an iron-silicon composite magnetic powder core and a preparation method and application thereof. The present invention prepares the composite magnetic powder core by compounding high-silicon iron silicon magnetic powder and low-silicon iron silicon magnetic powder. Among them, the high-silicon iron silicon magnetic powder has excellent magnetic properties. By limiting the silicon content of the high-silicon iron silicon magnetic powder to a certain range, the magnetic permeability of the magnetic powder core can be improved and the magnetic loss can be reduced. However, the density of the prepared magnetic powder core is low and the cost is high, which will affect the thermal stability of the magnetic powder core; the low-silicon iron silicon magnetic powder is soft in texture, low in cost, and easy to shape. The composite magnetic powder core prepared by the present invention has high density and excellent thermal stability, as well as high magnetic permeability and low magnetic loss.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In the first aspect, the present invention provides a method for preparing an iron-silicon composite magnetic powder core, the preparation method comprising the following steps: mixing high-silicon iron silicon magnetic powder and low-silicon iron silicon magnetic powder to obtain a mixed iron silicon powder material, and then sequentially performing passivation, insulation coating, press molding and annealing treatment to obtain the composite magnetic powder core; the silicon content of the high-silicon iron silicon magnetic powder is 6wt%-7.5wt%; the silicon content of the low-silicon iron silicon magnetic powder is 3.5wt%-4.5wt%.

[0008] Specifically, the silicon content of the high-silicon iron silicon magnetic powder can be 6wt%, 6.5wt%, 7wt%, 7.2wt% or 7.5wt%, and the silicon content of the low-silicon iron silicon magnetic powder can be 3.5wt%, 3.7wt%, 4wt%, 4.2wt% or 4.5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0009] The present invention prepares a composite magnetic powder core by compounding high silicon iron silicon magnetic powder and low silicon iron silicon magnetic powder. Among them, the high silicon iron silicon magnetic powder has excellent magnetic properties. By limiting the silicon content of the high silicon iron silicon magnetic powder within a certain range, the magnetic permeability of the magnetic powder core can be improved and the magnetic loss can be reduced. However, the density of the prepared magnetic powder core is low and the cost is high, which will affect the thermal stability of the magnetic powder core; the low silicon iron silicon magnetic powder is soft in texture, low in cost, and easy to shape. The composite magnetic powder core prepared by the present invention has high density and excellent thermal stability, high magnetic permeability, and low magnetic loss.

[0010] Preferably, the average particle size of the high silicon iron silicon magnetic powder is 600 mesh-1000 mesh, for example, it can be 600 mesh, 700 mesh, 800 mesh, 900 mesh or 1000 mesh, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0011] The present invention achieves particle size grading by regulating the particle sizes of high-silicon iron silicon magnetic powder and low-silicon iron silicon magnetic powder, and the density of the prepared iron-silicon composite magnetic powder core can be further improved, thereby improving the magnetic properties of the iron-silicon composite magnetic powder core.

[0012] Preferably, the high silicon iron silicon magnetic powder comprises a high silicon iron silicon magnetic powder with a silicon content or a combination of at least two high silicon iron silicon magnetic powders with a silicon content. Typical but non-limiting combinations include a combination of high silicon iron silicon magnetic powder with a silicon content of 6wt% and a high silicon iron silicon magnetic powder with a silicon content of 6.5wt%, or a combination of high silicon iron silicon magnetic powder with a silicon content of 6wt%, high silicon iron silicon magnetic powder with a silicon content of 6.5wt% and high silicon iron silicon magnetic powder with a silicon content of 7wt%.

[0013] Preferably, the average particle size of the low silicon iron silicon magnetic powder is 100 mesh-250 mesh, for example, it can be 100 mesh, 150 mesh, 200 mesh, 220 mesh or 250 mesh, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] Preferably, the low SiFeSi magnetic powder comprises one silicon content low SiFeSi magnetic powder or a combination of at least two silicon content low SiFeSi magnetic powders. Typical but non-limiting combinations include a combination of low SiFeSi magnetic powder with a silicon content of 3.5wt% and a low SiFeSi magnetic powder with a silicon content of 4wt%, or a combination of low SiFeSi magnetic powder with a silicon content of 3.5wt%, low SiFeSi magnetic powder with a silicon content of 4wt% and low SiFeSi magnetic powder with a silicon content of 4.5wt%.

[0015] Preferably, the mass ratio of the high silicon iron silicon magnetic powder to the low silicon iron silicon magnetic powder is (6-9):(1-4), for example, it can be 6:4, 6:1, 8:3, 9:1 or 9:4, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] The present invention can further improve the density of the iron-silicon composite magnetic powder core and further improve the magnetic permeability of the composite magnetic powder core and reduce its magnetic loss by further regulating the mass ratio of high-silicon iron-silicon magnetic powder and low-silicon iron-silicon magnetic powder.

[0017] Preferably, the mixing method comprises ball milling.

[0018] Preferably, before the mixing, the high silicon iron silicon magnetic powder and the low silicon iron silicon magnetic powder are pre-treated.

[0019] Preferably, the pretreatment holding temperature is 650°C-800°C, for example, 650°C, 670°C, 700°C, 750°C, 780°C or 800°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] Preferably, the pretreatment insulation time is 2h-3h, for example, it can be 2h, 2.2h, 2.4h, 2.6h, 2.8h or 3h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] The present invention can further eliminate stress in the magnetic powder by further regulating the pretreatment holding temperature and holding time, and can also further regulate the crystal phase of the magnetic powder to prevent the generation of impurity phases due to side reactions, which may lead to a decrease in the magnetic properties of the composite magnetic powder core.

[0022] Preferably, the cooling rate after pretreatment is 20°C / h-30°C / h, for example, it can be 20°C / h, 22°C / h, 24°C / h, 26°C / h, 28°C / h or 30°C / h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] Preferably, the pretreatment environment atmosphere includes a vacuum atmosphere or an inert gas atmosphere.

[0024] Preferably, the inert gas atmosphere includes any one of hydrogen, nitrogen or argon, or a combination of at least two of them. Typical but non-limiting combinations include a combination of hydrogen and nitrogen, or a combination of hydrogen, nitrogen and argon.

[0025] Preferably, the passivation comprises stirring and mixing the mixed iron silicon powder with the passivator and the solvent, and drying to obtain the passivated magnetic powder.

[0026] Preferably, the passivating agent comprises a water-soluble inorganic material.

[0027] Preferably, the water-soluble inorganic material includes phosphoric acid and / or aluminum dihydrogen phosphate.

[0028] Preferably, the solvent includes any one of deionized water, acetone or anhydrous ethanol or a combination of at least two of them. Typical but non-limiting combinations include a combination of deionized water and acetone, or a combination of deionized water, acetone and anhydrous ethanol.

[0029] Preferably, the drying comprises any one of natural drying, heated drying or vacuum drying, or a combination of at least two of them. Typical but non-limiting combinations include a combination of natural drying and heated drying, or a combination of natural drying, heated drying and vacuum drying.

[0030] Preferably, the drying insulation temperature is 80°C-120°C, for example, 80°C, 90°C, 100°C, 110°C or 120°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the drying heat preservation time is 20 min-40 min, for example, it can be 20 min, 25 min, 30 min, 35 min or 40 min, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0032] Preferably, the mass addition amount of the water-soluble inorganic material is 0.1%-1% of the mass of the mixed iron silicon powder, for example, it can be 0.1%, 0.3%, 0.5%, 0.7%, 0.9% or 1%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] Preferably, the insulation coating comprises mixing and stirring the passivated magnetic powder with the insulation coating coating agent, and then drying, crushing and sieving in sequence to obtain the insulation coated magnetic powder.

[0034] Preferably, the coating agent of the insulating coating includes modified insulating glue.

[0035] Preferably, the modified insulating adhesive solution includes a mixed solution of silica sol, a silane coupling agent and polyurethane.

[0036] Preferably, the average particle size of the colloidal particles of the modified insulating adhesive is ≤100 nm, for example, it can be 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the mass addition amount of the modified insulating glue is 1%-2% of the mass of the mixed iron-silicon powder, for example, it can be 1%, 1.2%, 1.5%, 1.7%, 1.9% or 2%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] Preferably, the drying comprises any one of natural drying, heating drying or vacuum drying, or a combination of at least two of them. Typical but non-limiting combinations include a combination of natural drying and heating drying, or a combination of natural drying, heating drying and vacuum drying.

[0039] Preferably, the mesh size of the sieving is 80-140 mesh, for example, it can be 80 mesh, 100 mesh, 120 mesh, 130 mesh or 140 mesh, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] Preferably, the pressing pressure is 1500 MPa-2000 MPa, for example, 1500 MPa, 1600 MPa, 1700 MPa, 1800 MPa, 1900 MPa or 2000 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] Preferably, the compression molding release agent comprises zinc stearate.

[0042] Preferably, the mass addition amount of the release agent is 0.2%-0.6% of the mass of the mixed iron silicon powder, for example, it can be 0.2%, 0.3%, 0.4%, 0.5% or 0.6%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] Preferably, the holding temperature of the annealing treatment is 680°C-720°C, for example, it can be 680°C, 690°C, 700°C, 710°C, 715°C or 720°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] Preferably, the holding time of the annealing treatment is 1 h-2 h, for example, 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h or 2 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] The present invention can further eliminate stress in the magnetic powder by further regulating the holding temperature and holding time of the annealing treatment, and can also regulate the crystal phase of the magnetic powder to prevent the generation of impurity phases due to side reactions, which leads to a decrease in the magnetic properties of the composite magnetic powder core.

[0046] Preferably, the atmosphere of the annealing treatment includes an inert gas atmosphere.

[0047] Preferably, the inert gas atmosphere comprises nitrogen and / or argon.

[0048] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0049] (1) Pre-treating high silicon iron silicon magnetic powder and low silicon iron silicon magnetic powder to obtain pre-treated high silicon iron silicon magnetic powder and low silicon iron silicon magnetic powder, wherein the pre-treatment is performed at a holding temperature of 650°C-800°C, the holding time of the pre-treatment is 2h-3h, and the cooling rate after the pre-treatment is 20°C / h-30°C / h.

[0050] (2) Pre-treated high-silicon iron silicon magnetic powder and pre-treated low-silicon iron silicon magnetic powder are mixed in proportion to obtain mixed iron silicon powder, wherein the mixing method includes ball milling.

[0051] (3) The mixed iron silicon powder and the passivator are stirred and mixed, and then dried to obtain passivated magnetic powder. The passivator includes an inorganic acid and a solvent. The drying insulation temperature is 80° C.-120° C., and the drying insulation time is 20 min-40 min.

[0052] (4) After the passivated magnetic powder and the insulating coating coating agent are mixed and stirred, they are dried, crushed and sieved in sequence to obtain the insulating coated magnetic powder, wherein the insulating coating coating agent includes a modified insulating glue, and the mesh size of the sieve is 80-140 mesh.

[0053] (5) After adding a release agent to the magnetic powder after insulation coating, the magnetic powder is placed in a press for compression molding to obtain a preformed composite magnetic powder core, wherein the compression molding pressure is 1500MPa-2000MPa.

[0054] (6) Annealing the preformed composite magnetic powder core at 680° C.-720° C. for 1 h-2 h to obtain the iron-silicon composite magnetic powder core.

[0055] In a second aspect, the present invention provides an iron-silicon composite magnetic powder core, which is prepared by the preparation method described in the first aspect.

[0056] In a third aspect, the present invention provides an application of the iron-silicon composite magnetic powder core as described in the second aspect, wherein the iron-silicon composite magnetic powder core is applied to the new energy field, the communication field or the automobile industry field.

[0057] Compared with the prior art, the present invention has at least the following beneficial effects:

[0058] (1) The present invention prepares a composite magnetic powder core by compounding high-silicon iron silicon magnetic powder and low-silicon iron silicon magnetic powder. Among them, high-silicon iron silicon magnetic powder has excellent magnetic properties. Limiting the silicon content of high-silicon iron silicon magnetic powder within a certain range can improve the magnetic permeability of the magnetic powder core and reduce magnetic loss. However, the density of the prepared magnetic powder core is low and the cost is high, which will affect the thermal stability of the magnetic powder core; low-silicon iron silicon magnetic powder is soft and easy to shape, and has low cost.

[0059] (2) The present invention further improves the density and magnetic properties of the composite magnetic powder core by further regulating the average particle size of high-silicon magnetic powder and low-silicon magnetic powder.

[0060] (3) The composite magnetic powder core prepared by the present invention has high density and excellent thermal stability, as well as high magnetic permeability and low magnetic loss. DETAILED DESCRIPTION

[0061] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0062] Example 1

[0063] This embodiment provides a method for preparing an iron-silicon composite magnetic powder core, the preparation method comprising the following steps:

[0064] (1) pre-treating high silicon iron silicon magnetic powder and low silicon iron silicon magnetic powder to obtain pre-treated high silicon iron silicon magnetic powder and low silicon iron silicon magnetic powder, wherein the pre-treating is performed at a holding temperature of 740° C., the holding time of the pre-treating is 2 h, the cooling rate after the pre-treating is 30° C. / h, and the pre-treating environment atmosphere is a vacuum atmosphere;

[0065] (2) mixing the pretreated high silicon iron silicon magnetic powder and the pretreated low silicon iron silicon magnetic powder in proportion to obtain a mixed iron silicon powder, wherein the mixing method includes ball milling, the high silicon iron silicon magnetic powder is a high silicon iron silicon magnetic powder with an average particle size of 1000 mesh and a silicon content of 6.5wt%, and the low silicon iron silicon magnetic powder is a low silicon iron silicon magnetic powder with an average particle size of 200 mesh and a silicon content of 4.5wt%, and the mass ratio of the high silicon iron silicon magnetic powder to the low silicon iron silicon magnetic powder is 8:2;

[0066] (3) stirring and mixing the mixed iron silicon powder with phosphoric acid and acetone, and drying to obtain passivated magnetic powder, wherein the mass addition amount of the phosphoric acid is 0.2% of the mass of the mixed iron silicon powder, the drying insulation temperature is 100° C., and the drying insulation time is 30 min;

[0067] (4) after mixing and stirring the passivated magnetic powder and the insulating coating coating agent, drying, crushing and sieving are performed in sequence to obtain the insulating coated magnetic powder, wherein the insulating coating coating agent comprises a modified insulating adhesive liquid, wherein the modified insulating adhesive liquid is a mixed solution of silica sol, a silane coupling agent and polyurethane, and the mass addition amount of the modified insulating adhesive liquid is 1.5% of the mass of the mixed iron silicon powder material, and the mesh number of the sieving is 140 meshes;

[0068] (5) adding zinc stearate to the magnetic powder after insulation coating, and placing the mixture in a press for compression molding to obtain a preformed composite magnetic powder core, wherein the mass addition amount of the zinc stearate is 0.4% of the mass of the mixed iron-silicon powder, and the compression molding pressure is 1900 MPa;

[0069] (6) The preformed composite magnetic powder core is annealed at 700° C. for 1 hour in a nitrogen atmosphere to obtain the iron-silicon composite magnetic powder core.

[0070] Example 2

[0071] This embodiment provides a method for preparing an iron-silicon composite magnetic powder core, the preparation method comprising the following steps:

[0072] (1) pre-treating high silicon iron silicon magnetic powder and low silicon iron silicon magnetic powder to obtain pre-treated high silicon iron silicon magnetic powder and low silicon iron silicon magnetic powder, wherein the pre-treating is performed at a holding temperature of 650° C., the holding time of the pre-treating is 3 h, the cooling rate after the pre-treating is 20° C. / h, and the pre-treating environment atmosphere is a nitrogen atmosphere;

[0073] (2) mixing the pretreated high silicon iron silicon magnetic powder and the pretreated low silicon iron silicon magnetic powder in proportion to obtain a mixed iron silicon powder, wherein the mixing method includes ball milling, the high silicon iron silicon magnetic powder is a combination of 7 parts by weight of 1000 mesh iron silicon magnetic powder with a silicon content of 6.5wt% and 3 parts by weight of 1000 mesh iron silicon magnetic powder with a silicon content of 7.5wt%, the low silicon iron silicon magnetic powder is a combination of 5 parts by weight of 100 mesh iron silicon magnetic powder with a silicon content of 3.5wt% and 5 parts by weight of 200 mesh iron silicon magnetic powder with a silicon content of 4.5wt%, and the mass ratio of the high silicon iron silicon magnetic powder to the low silicon iron silicon magnetic powder is 9:1;

[0074] (3) stirring and mixing the mixed iron silicon powder, aluminum dihydrogen phosphate and anhydrous ethanol, and drying to obtain passivated magnetic powder, wherein the mass addition amount of the aluminum dihydrogen phosphate is 0.1% of the mass of the mixed iron silicon powder, the drying insulation temperature is 120° C., and the drying insulation time is 20 min;

[0075] (4) after mixing and stirring the passivated magnetic powder and the insulating coating coating agent, drying, crushing and sieving are performed in sequence to obtain the insulating coated magnetic powder, wherein the insulating coating coating agent comprises a modified insulating adhesive liquid, wherein the modified insulating adhesive liquid is a mixed solution of silica sol, a silane coupling agent and polyurethane, and the mass addition amount of the modified insulating adhesive liquid is 1% of the mass of the mixed iron silicon powder material, and the mesh number of the sieving is 80 meshes;

[0076] (5) adding zinc stearate to the magnetic powder after insulation coating, and placing the mixture in a press for compression molding to obtain a preformed composite magnetic powder core, wherein the mass addition amount of the zinc stearate is 0.2% of the mass of the mixed iron-silicon powder, and the compression molding pressure is 1500 MPa;

[0077] (6) The preformed composite magnetic powder core is annealed at 680° C. for 2 h in an argon atmosphere to obtain the iron-silicon composite magnetic powder core.

[0078] Example 3

[0079] This embodiment provides a method for preparing an iron-silicon composite magnetic powder core, the preparation method comprising the following steps:

[0080] (1) pre-treating high silicon iron silicon magnetic powder and low silicon iron silicon magnetic powder to obtain pre-treated high silicon iron silicon magnetic powder and low silicon iron silicon magnetic powder, wherein the pre-treating is performed at a holding temperature of 800° C., the holding time of the pre-treating is 2 h, the cooling rate of the pre-treating is 25° C. / h, and the ambient atmosphere of the pre-treating is an argon atmosphere;

[0081] (2) mixing the pretreated high silicon iron silicon magnetic powder and the pretreated low silicon iron silicon magnetic powder in proportion to obtain a mixed iron silicon powder, wherein the mixing method includes ball milling, the high silicon iron silicon magnetic powder is a combination of 5 parts by weight of 700 mesh iron silicon magnetic powder with a silicon content of 6wt%, 2 parts by weight of 800 mesh iron silicon magnetic powder with a silicon content of 7wt% and 3 parts by weight of 1000 mesh iron silicon magnetic powder with a silicon content of 7.5wt%, the low silicon iron silicon magnetic powder is a combination of 2 parts by weight of 200 mesh iron silicon magnetic powder with a silicon content of 3.5wt%, 2 parts by weight of 150 mesh iron silicon magnetic powder with a silicon content of 4wt% and 6 parts by weight of 100 mesh iron silicon magnetic powder with a silicon content of 4.5wt%, and the mass ratio of the high silicon iron silicon magnetic powder to the low silicon iron silicon magnetic powder is 6:4;

[0082] (3) stirring and mixing the mixed iron silicon powder, phosphoric acid and deionized water, and drying to obtain passivated magnetic powder, wherein the phosphoric acid is added in an amount of 1% by mass of the mixed iron silicon powder, the drying insulation temperature is 80° C., and the drying insulation time is 40 min;

[0083] (4) after mixing and stirring the passivated magnetic powder and the insulating coating coating agent, drying, crushing and sieving are performed in sequence to obtain the insulating coated magnetic powder, wherein the insulating coating coating agent comprises a modified insulating adhesive liquid, wherein the modified insulating adhesive liquid is a mixed solution of silica sol, a silane coupling agent and polyurethane, and the mass addition amount of the modified insulating adhesive liquid is 2% of the mass of the mixed iron silicon powder material, and the mesh number of the sieving is 140 meshes;

[0084] (5) adding zinc stearate to the magnetic powder after insulation coating, and placing the mixture in a press for compression molding to obtain a preformed composite magnetic powder core, wherein the mass addition amount of the zinc stearate is 0.6% of the mass of the mixed iron-silicon powder, and the compression molding pressure is 2000 MPa;

[0085] (6) The preformed composite magnetic powder core is annealed at 720° C. for 1 hour in a nitrogen atmosphere to obtain the iron-silicon composite magnetic powder core.

[0086] Example 4

[0087] The difference between this embodiment and embodiment 1 is that, except that the average particle size of the high silicon iron silicon magnetic powder in step (2) is 550 mesh, the rest is the same as embodiment 1.

[0088] Example 5

[0089] The difference between this embodiment and embodiment 1 is that, except that the average particle size of the high silicon iron silicon magnetic powder in step (2) is 1050 mesh, the rest is the same as embodiment 1.

[0090] Example 6

[0091] The difference between this embodiment and embodiment 1 is that, except that the average particle size of the low-silicon iron silicon magnetic powder in step (2) is 50 mesh, the rest is the same as embodiment 1.

[0092] Example 7

[0093] The only difference between this embodiment and embodiment 1 is that, except that the average particle size of the low-silicon iron silicon magnetic powder in step (2) is 300 mesh, the rest is the same as embodiment 1.

[0094] Example 8

[0095] The only difference between this embodiment and embodiment 1 is that, except that the high silicon ferrosilicon magnetic powder in step (2) is a combination of 7 parts by mass of 1000 mesh ferrosilicon magnetic powder with a silicon content of 6.5wt% and 3 parts by mass of 1000 mesh ferrosilicon magnetic powder with a silicon content of 7.5wt%, the rest is the same as embodiment 1.

[0096] Example 9

[0097] The only difference between this embodiment and embodiment 1 is that, except that the low silicon ferrosilicon magnetic powder in step (2) is a combination of 5 parts by mass of 100 mesh ferrosilicon magnetic powder with a silicon content of 3.5 wt% and 5 parts by mass of 200 mesh ferrosilicon magnetic powder with a silicon content of 4.5 wt%, the rest is the same as embodiment 1.

[0098] Example 10

[0099] The difference between this embodiment and embodiment 1 is that, except for the mass ratio of high silicon iron silicon magnetic powder to low silicon iron silicon magnetic powder in step (2) being 5:5, the rest is the same as embodiment 1.

[0100] Embodiment 11

[0101] The difference between this embodiment and embodiment 1 is that, except for the mass ratio of high silicon iron silicon magnetic powder to low silicon iron silicon magnetic powder in step (2) being 9.5:0.5, the rest is the same as embodiment 1.

[0102] Example 12

[0103] The only difference between this embodiment and embodiment 1 is that, except that the holding temperature of the pretreatment in step (1) is 600° C., the rest is the same as embodiment 1.

[0104] Embodiment 13

[0105] The only difference between this embodiment and embodiment 1 is that, except that the holding temperature of the pretreatment in step (1) is 850° C., the rest is the same as embodiment 1.

[0106] Embodiment 14

[0107] The only difference between this embodiment and embodiment 1 is that, except that the holding temperature of the annealing treatment in step (6) is 650° C., the rest is the same as embodiment 1.

[0108] Embodiment 15

[0109] The only difference between this embodiment and embodiment 1 is that, except that the holding temperature of the annealing treatment in step (6) is 750° C., the rest is the same as embodiment 1.

[0110] Comparative Example 1

[0111] The difference between this comparative example and Example 1 is that, except that the silicon content of the high-silicon iron silicon magnetic powder in step (2) is 8%, the rest is the same as Example 1.

[0112] Comparative Example 2

[0113] The difference between this comparative example and Example 1 is that, except that the silicon content of the high-silicon iron silicon magnetic powder in step (2) is 5.5%, the rest is the same as Example 1.

[0114] Comparative Example 3

[0115] The difference between this comparative example and Example 1 is that, except that the silicon content of the low-silicon iron silicon magnetic powder in step (2) is 3%, the rest is the same as Example 1.

[0116] Comparative Example 4

[0117] The difference between this comparative example and Example 1 is that, except that the silicon content of the low-silicon iron silicon magnetic powder in step (2) is 5%, the rest is the same as Example 1.

[0118] Test Method

[0119] The composite magnetic powder cores obtained in Examples 1 to 15 and Comparative Examples 1 to 4 were made into magnetic rings with an outer diameter of 12.7 mm, an inner diameter of 7.6 mm and a height of 3 mm, and the density ρ of the magnetic core was tested by the drainage method. Subsequently, the magnetic core was wound, and the inductance L was tested by an LCR meter to calculate the effective magnetic permeability μ of the annular magnetic core, and the test frequency was 100 kHz. The AC loss of the magnetic core was tested by an Iwasaki SY-8218 soft magnetic BH analyzer from Japan, and the test conditions were: 50 kHz, 100 mT, and a temperature of 25°C. The results of the effective magnetic permeability μ, AC loss Pcv and density ρ of the magnetic core are recorded in Table 1.

[0120] Table 1

[0121] μ(H / m) <![CDATA[Pcv(mW / cm 3 )]]> <![CDATA[Ρ(g / cm 3 )]]> Example 1 78 385 6.85 Example 2 73 401 6.75 Example 3 70 410 6.68 Example 4 68 422 6.66 Example 5 66 432 6.61 Example 6 67 429 6.59 Example 7 63 445 6.55 Example 8 65 435 6.58 Example 9 62 445 6.56 Example 10 64 438 6.57 Embodiment 11 66 425 6.61 Example 12 67 423 6.62 Embodiment 13 65 427 6.60 Embodiment 14 62 452 6.53 Embodiment 15 64 443 6.54 Comparative Example 1 58 458 6.52 Comparative Example 2 55 460 6.48 Comparative Example 3 59 454 6.49 Comparative Example 4 57 457 6.51

[0122] The test results show that:

[0123] (1) It can be seen from Examples 1 to 15 and Comparative Examples 1 to 4 that the present invention prepares a composite magnetic powder core by compounding high silicon iron silicon magnetic powder and low silicon iron silicon magnetic powder. Among them, high silicon iron silicon magnetic powder has excellent magnetic properties. Limiting the silicon content of high silicon iron silicon magnetic powder within a certain range can improve the magnetic permeability of the magnetic powder core and reduce magnetic loss. However, the density of the prepared magnetic powder core is low and the cost is high, which will affect the thermal stability of the magnetic powder core; low silicon iron silicon magnetic powder is soft and easy to shape, and has low cost. The composite magnetic powder core prepared by the present invention has high density and excellent thermal stability, as well as high magnetic permeability and low magnetic loss.

[0124] (2) It can be seen from Examples 1 and 4 to 7 that the present invention further improves the density and magnetic properties of the composite magnetic powder core by adjusting the average particle size of the high-silicon magnetic powder and the low-silicon magnetic powder.

[0125] (3) It can be seen from Examples 1 and 8 to 11 that the present invention can ensure the consistency of the iron silicon magnetic powder by further regulating the composition types and mass ratio of the high silicon iron silicon magnetic powder and the low silicon iron silicon magnetic powder, thereby facilitating pressing and molding, and the density and magnetic properties of the prepared composite magnetic powder core are further improved.

[0126] (4) It can be seen from Examples 1 and 12 to 15 that the density and magnetic properties of the composite magnetic powder core prepared by the present invention are further improved by further regulating the holding temperature of the pretreatment and annealing treatment.

[0127] In summary, the present invention prepares a composite magnetic powder core by compounding high silicon iron silicon magnetic powder and low silicon iron silicon magnetic powder. Among them, high silicon iron silicon magnetic powder has excellent magnetic properties. Limiting the silicon content of high silicon iron silicon magnetic powder within a certain range can improve the magnetic permeability of the magnetic powder core and reduce magnetic loss. However, the density of the prepared magnetic powder core is low and the cost is high, which will affect the thermal stability of the magnetic powder core; low silicon iron silicon magnetic powder is soft and easy to shape, and has low cost. The present invention further improves the density and magnetic properties of the composite magnetic powder core by regulating the average particle size of high silicon magnetic powder and low silicon magnetic powder. The composite magnetic powder core prepared by the present invention has high density and excellent thermal stability, high magnetic permeability and low magnetic loss.

[0128] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing an iron-silicon composite magnetic powder core, characterized in that: The preparation method comprises the following steps: Mixing high-silicon iron silicon magnetic powder and low-silicon iron silicon magnetic powder to obtain a mixed iron silicon powder material, and then sequentially performing passivation, insulation coating, compression molding and annealing treatment to obtain the iron silicon composite magnetic powder core; The silicon content of the high silicon iron silicon magnetic powder is 6wt%-7.5wt%; The silicon content of the low-silicon iron silicon magnetic powder is 3.5wt%-4.5wt%.

2. The preparation method according to claim 1, characterized in that: The average particle size of the high silicon iron silicon magnetic powder is 600 mesh to 1000 mesh; Preferably, the average particle size of the low-silicon iron silicon magnetic powder is 100 mesh-250 mesh.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the high silicon iron silicon magnetic powder to the low silicon iron silicon magnetic powder is (6-9):(1-4).

4. The preparation method according to any one of claims 1 to 3, characterized in that Before the mixing, the high silicon iron silicon magnetic powder and the low silicon iron silicon magnetic powder are also pre-treated; Preferably, the pretreatment holding temperature is 650°C-800°C; Preferably, the pretreatment holding time is 2h-3h.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The passivating agent comprises a water-soluble inorganic material; Preferably, the mass addition amount of the water-soluble inorganic material is 0.1%-1% of the mass of the mixed iron silicon powder.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The coating agent of the insulation coating includes a modified insulation glue; Preferably, the mass addition amount of the modified insulating glue is 1%-2% of the mass of the mixed iron-silicon powder.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The compression molding pressure is 1500MPa-2000MPa; Preferably, the compression molding release agent comprises zinc stearate; Preferably, the mass addition amount of the release agent is 0.2%-0.6% of the mass of the mixed iron silicon powder.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The holding temperature of the annealing treatment is 680°C-720°C; Preferably, the holding time of the annealing treatment is 1h-2h.

9. An iron-silicon composite magnetic powder core, characterized in that: The iron-silicon composite magnetic powder core is prepared by the preparation method described in any one of claims 1 to 8.

10. An application of the iron-silicon composite magnetic powder core as claimed in claim 9, characterized in that: The iron-silicon composite magnetic powder core is applied in the fields of new energy, communication or automobile industry.

Citation Information

Patent Citations

  • Gas atomization iron-silicon-aluminum soft magnetic composite material with low-medium frequency loss

    CN111029076A